Lloyd Brown interviewed by Hamish Sewell in the Australian generations oral history project. - Brown, Lloyd Dennis, 1945-; Sewell, Hamish, 1964- (2014)
Part of the Builders generation (born between 1925-46).
Catalogue record generated as part of a batch load.
Recorded on 3 April 2014 in Brisbane, Queensland.
Mode of access: Online.
Timed summary (5 pages)
Keywords: Brown, Lloyd Dennis, -- 1945- -- Interviews; Australia. -- Royal Australian Air Force -- Officers -- Interviews; Farmers -- Queensland -- Interviews; Grazing -- Queensland; Air pilots, Military -- Australia -- Interviews; Vietnam War, 1961-1975 -- Personal narratives, Australian; Age-structured populations -- Australia; Intergenerational relations -- Australia